Laparoscopic guided luteal injection of PGF2alpha for synchronization of oestrus in cows - SHARMA, R K; RAWAL, C V S; HOQUE, M (The Indian Journal of Animal Reproduction, 2003)
Luteal injection of PGF2a was effective in inducing oestrus in all treated cows. The mean intervalbetween treatment and appearance of oestrus was marginally shorter with luteal injection of 30 μg(57.17±4.83 h) as compared to 750 μg Tiaprost given intramuscularly (62.18±4.83 h). Results of presentstudy suggested that luteal injection of reduced dose of PGF2a (1/25th) was as effective as high dosewith 1/M route for induction of oestrus in cyclic cows.
Keywords: Laparoscopy; PGF2alpha; Synchronization of oestrus; CL